EXPLORING EFL LEARNERS’ ENGLISH LANGUAGE ANXIETY IN BUSINESS PRESENTATION IN HIGHER EDUCATION - Ryani Yulian; Ufi Ruhama (English Education Department, 2020)
University students must be situated in a learning repertoire situation since conventional lecture is no longer used as the best way to engage students in active learning. Students of the Faculty of Economics and Business at Universitas Muhammadiyah Pontianak are required to perform business presentation simulation collectively as one of the course requirements to pass Business English subject. Therefore, this research was aimed at examining the affective factors particularly the students’ language anxiety in simulation because the success of a presentation is not only isolated in a cognitive domain but also the affective domain as well. This research employed fifty participants from second-semester students at the Faculty of Economics and Business at Universitas Muhammadiyah Pontianak as the samples. Data from questionnaires were triangulated with direct observation and in-depth interviews. The findings indicated that students experienced High Language Anxiety (61,99), a variety of attributes of anxiety in terms of psychological state, and fears of negative evaluations from lecturer and peers. It suggests outcomes to evaluate the coursebook of Business English in the university and to have a better implementation of simulation with accommodative learning materials, instructions, and activities. The students’ language anxiety analysis in business presentation simulation is to justify the applicability of business presentation activity in the classroom for long-term use.